Power And Will Reflected In Clint Eastwood's J. Edgar Movie (2011): A Psychoanalytic Approach - Sari, Faradila Ratna, Dr. Phil. Dewi Candraningrum, S.Pd., M.Ed, Drs. Abdillah Nugroho, M. Hum. (2013)
In this research, the researcher discusses power and will of major characters in J. Edgar movie. Objectives of the research are: to analyze power and will in J. Edgar movie based on its structural elements and a psychoanalytic approach. The type of the research is qualitative research. There are two types of the data, namely primary and secondary data. Primary data source comes from J. Edgar movie and secondary data comes from books, internet, or any information related to the study. Then, the data is analyzed based on structural elements and psychoanalytic approach proposed by Sigmund Freud. In analyzing the data, the researcher uses descriptive analysis. The writer draws the conclusion of the research, as follows; first, based on the structural analysis of each element, it shows that the character and characterization, plot, setting, point of view, theme, mise en scene, casting, cinematography, sound, and editing are correlated to each other and form of unity. Second, based on the psychoanalytic analysis is focused on major characters of J. Edgar movie reflected in id, ego, and superego. The last, based on the power and will issues, this research paper is focused on major characters in J. Edgar movie. Based on psychoanalytic approach J. Edgar includes in the term of being powerful person. J. Edgar Hoover with his power and will character was developed his carrier and his perspective to solve the problem